2004
DOI: 10.1038/sj.ijo.0802644
|View full text |Cite
|
Sign up to set email alerts
|

Response of the alternative complement pathway to an oral fat load in first-degree relatives of subjects with type II diabetes

Abstract: OBJECTIVE:To investigate levels of components of the alternative pathway of complement, and of two activation products, ASP and Bb, in persons ranging in insulin resistance both fasting and following the consumption of a high-fat, low-carbohydrate meal. SUBJECTS: Healthy controls (n ¼ 17) and normoglycaemic first-degree relatives of patients with type II diabetes (n ¼ 15). MEASUREMENTS: All subjects had normal glucose tolerance. Blood was collected for the measurement of plasma glucose, insulin, triglycerides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Cross-sectional studies have shown that obesity is associated with elevated plasma levels of C3 [4,[6][7][8][9][10], but the causal and temporal relations of this association have been unclear. The present study showed that C3 was strongly associated both with weight at baseline and weight at follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies have shown that obesity is associated with elevated plasma levels of C3 [4,[6][7][8][9][10], but the causal and temporal relations of this association have been unclear. The present study showed that C3 was strongly associated both with weight at baseline and weight at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are overweight or obese generally have raised concentrations of C3 and C4 [4][5][6][7][8][9][10], and it has been reported that C3 levels decrease after weight loss [6,7]. The proteolytic fragment of C3, acylation-stimulating protein (ASP), is a paracrine metabolic factor that stimulates the uptake of glucose and fat storage in human adipose tissue [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these proteins is increased in response to inflammation and infection but at a slower rate than for traditional acute phase proteins (1,2). Both C3 and C4 have shown substantial correlations with obesity (3)(4)(5)(6), and high gene expression of these complement components has been reported in omental adipose tissue in obese men (3). High C3 levels have been reported in subjects with diabetes and insulin resistance (6 -9).…”
mentioning
confidence: 86%
“…Levels of CFB and C3 were also higher in subjects with insulin resistance and other features of the metabolic syndrome (25). CFB is produced by adipose tissue where they likely influence the production of the anaphylatoxin C3a and its carboxypeptidase B-anaphylatoxic-inactivated derivative C3adesArg (ASP).…”
Section: Discussionmentioning
confidence: 96%
“…The activation of the alternative pathway of the complement system could be a link between obesity and obesity-related metabolic disorders since CFB is expressed by adipose tissue and upregulated in obese and/or IGT subjects (23)(24)(25). CFB may influence the production of acylation-stimulating protein (ASP), which could play an important role in the regulation of fatty acid uptake and triglycerides formation (26).…”
Section: Introductionmentioning
confidence: 99%